Structure activity relationship of pyridoxazinone substituted RHS analogs of oxabicyclooctane-linked 1, 5-naphthyridinyl novel bacterial topoisomerase inhibitors as broad-spectrum antibacterial agents (Part-6). Issue 17 (1st September 2015) - Singh, Sheo B.; Kaelin, David E.; Wu, Jin; Miesel, Lynn; Tan, Christopher M.; Meinke, Peter T.; Olsen, David B.; Lagrutta, Armando; Wei, Changqing; Liao, Yonggang; Peng, Xuanjia; Wang, Xiu; et al.
Graphical abstract